Developing a relationship with nature and place: the potential role of forest school. Issue 8 (3rd August 2021) - Harris, Frances
Abstract: Outdoor learning provides an opportunity for schools to foster children's engagement with nature. This paper focusses on forest school practitioners' perceptions of children's development of a relationship with nature and the place where forest school occurs, through interviews with forest school activity leaders. Reflecting on literature, the analysis of interviews sought to identify the processes through which attachment to place or connection to nature occurs. The findings suggest that through regular and repeated activities in a natural setting at forest school, children become more relaxed, overcome any fears, have fun, connect with nature as they come to know it better, and develop an affinity for the location. Further, they develop a sense of ownership and concern for the forest school setting and desire to protect it. For some forest school practitioners, fostering a relationship with nature and place, and developing pro-environmental behaviour, is a fundamental part of their practice.